2021
DOI: 10.1002/ajh.26339
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular abnormalities in Waldenström's macroglobulinemia patients: Correlations and prognostic impact

Abstract: While Waldenström macroglobulinemia (WM) is characterized by an almost unifying mutation in MYD88, clinical presentation at diagnosis and response to therapy can be widely different among WM patients. Current prognostic tools only partially address this clinical heterogeneity. Limited data compiling both molecular and cytogenetic information have been used in risk prognostication in WM. To investigate the clinical impact of genetic alterations in WM, we evaluated cytogenetic and molecular abnormalities by chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…20 Factors that influenced the risk of relapse post-auto-HCT were complex karyotype and increased lines of prior therapy, however there were only two patients with complex karyotype in our data which limited our power to make definitive However, the prognostic factors that were associated with shorter PFS included highly complex karyotype (p = 0.01) and lower OS (p < 0.05). 21 Wang et al, also reported complex karyotype was associated with significantly shorter OS, PFS, and time to treatment. 22 Of the 48 patients transplanted in our cohort during the time period of 2007 and 2017, 22 relapsed after auto-HCT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…20 Factors that influenced the risk of relapse post-auto-HCT were complex karyotype and increased lines of prior therapy, however there were only two patients with complex karyotype in our data which limited our power to make definitive However, the prognostic factors that were associated with shorter PFS included highly complex karyotype (p = 0.01) and lower OS (p < 0.05). 21 Wang et al, also reported complex karyotype was associated with significantly shorter OS, PFS, and time to treatment. 22 Of the 48 patients transplanted in our cohort during the time period of 2007 and 2017, 22 relapsed after auto-HCT.…”
Section: Discussionmentioning
confidence: 97%
“…Others have also explored the impact of cytogenetic and molecular abnormalities on outcomes of newly diagnosed WM receiving frontline therapy and discovered that they did not significantly impact time to first treatment and response to therapy. However, the prognostic factors that were associated with shorter PFS included highly complex karyotype ( p = 0.01) and lower OS ( p < 0.05) 21 . Wang et al., also reported complex karyotype was associated with significantly shorter OS, PFS, and time to treatment 22 …”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 219 patients, Krzisch et al found that 35% of del(6q) cases harbored CXCR4 mutations, as detected by chromosomal banding analysis (CBA), FISH, and targeted MPS. Moreover, a significantly more complex karyotype was shown in patients with del(6q) [110].…”
Section: Q21 Deletionmentioning
confidence: 99%
“…Albeit at low frequency, other recurring somatic mutations have been reported, including ARID1A (17%), CD79B, KMT2D (or MLL2), MYBBP1A and TP53 (<15% of cases each) (Table 3, Figure 2C) [26][27][28]. [110] Using MPS in a large series of WM and IgM-MGUS patients, Varettoni et al (2017) demonstrated subclonal mutations in KMT2D (16%), TP53 (8%), NOTCH2 (7%), PRDM1 (4%), ARID1A (3%), CD79B (3%) and TRAF3 (1%), while no mutations were found in MYBBP1A and TNFAIP3 [10]. Of note, the median number of KMT2D mutations was significantly higher in WM compared to IgM-MGUS patients.…”
Section: Infrequent Dna Mutationsmentioning
confidence: 99%
“…The mechanisms of resistance are, in general, common to other types of malignant tumors, involving the overexpression of efflux drug transporters, mutations in TP53 and overexpression of oncogenic pathways, such as the mitogen-activated protein kinase (MAPK) and the PI3K/AKT cascades ( 28 , 29 ). Despite several cytogenetic and molecular alterations have been recognized to possess a prognostic role in LPL/WM, their precise significance in the resistance to chemotherapeutic drugs is still unknown ( 30 ).…”
Section: Mechanisms Of Drug Resistance In Lpl/wmmentioning
confidence: 99%